Multiple truths in planning? A comment regarding postmodern ideas in planning theory - Lintz, Gerd (Raumforschung und Raumordnung | Spatial Research and Planning, 2024)
In a recently published essay on planning theory, Benjamin Davy, Meike Levin-Keitel and Franziska Sielker observe a “brutal plurality of truths” that complicates spatial planning. In particular, they ask how planners can deal with this. Against the backdrop of the climate and biodiversity crisis, the commentary takes this essay as an opportunity to take a critical look at the multiplicity of truths postulated by postmodernism and the correspondingly stretched concept of knowledge. Above all, it points out the great importance of the pursuit of truth (in the singular) for society. Moreover, it emphasises the danger of making inter- and transdisciplinary research more difficult, of depreciating science and of increasing the distance between science and the centre of society. The commentary pleads for a faster, stronger focus on the very big challenges of our time, for which a pragmatic orientation towards truth and what unites society is indispensable.